2011
DOI: 10.1002/jbm.b.31794
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of strength, fatigue durability, and disassembly of Ti6Al4V and CoCrMo necks in modular total hip replacements

Abstract: Modularity in total hip replacement offers advantages with regard to biomechanical adjustments and leg lengths. Recently, modular femoral necks were introduced as an added advantage to head modularity permitting further adjustments in femoral version as well as offset and ease of revision. Currently, most necks are made of Ti6Al4V for which cases of in vivo fractures and inseparable neck-stem junctions have been reported. Therefore, we investigated CoCrMo head-Ti6Al4V stem hip replacements with necks made of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
0
15
0
2
Order By: Relevance
“…Introducing an angle in the neck eliminates the ability to achieve such a goal and explains the decreased stability seen in the 8° and 15° necks in this study. Failure of dual taper implants related to complications including corrosion at the NS interface, adverse local tissue reaction, and neck fracture has led to decreased utilization and recall of these implants and negated the theoretical benefits achieved with the additional modular interface [9]. Nonetheless, revision cases of failed implants will continue to be a challenge that orthopaedic surgeons face, and understanding the mechanism by which these complications and failures occur may provide us insight for future direction in designing new implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introducing an angle in the neck eliminates the ability to achieve such a goal and explains the decreased stability seen in the 8° and 15° necks in this study. Failure of dual taper implants related to complications including corrosion at the NS interface, adverse local tissue reaction, and neck fracture has led to decreased utilization and recall of these implants and negated the theoretical benefits achieved with the additional modular interface [9]. Nonetheless, revision cases of failed implants will continue to be a challenge that orthopaedic surgeons face, and understanding the mechanism by which these complications and failures occur may provide us insight for future direction in designing new implants.…”
Section: Discussionmentioning
confidence: 99%
“…While several theories exist as to etiologies of wear-particle generation and subsequent corrosion at the modular interface, research suggests that the process begins with mechanical fretting and disruption of the protective oxide layer leading to the release of metal ions at the taper interface [7], [8]. Both the debris and corrosion at the modular surface can have a multitude of effects on the outcome of the prosthesis including osteolysis, adverse local tissue reactions, increased risk of neck failure or fracture, and increased distraction force requirements at revision surgery [9]. It has been postulated that the process of fretting may begin at impaction of the components at index surgery [4], thus indicating the importance of proper engagement and stability of the components to prevent micromotion and subsequent fretting corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies 12,13 showed that test environments similar to body conditions (bovine serum at 37˚C body temperature) cannot replicate wear and corrosion damages observed on in vivo implant retrievals within the duration of typical in vitro tests. They would require excessive test durations (months or even years) in order to reproduce damages that occur in patients over the typical implant service life of years or decades.…”
Section: In Vitro Simulation Setupmentioning
confidence: 99%
“…2A) was applied using a MTS 858 Mini Bionix 1 II testing machine (MTS Systems Corporation; Eden Prairie, MN), with a 10 Hz cyclic loading frequency, as previously described. 12,13 About 12 h of loading and 12 h of resting cycles were used to increase the effects of wear-corrosion damage on the modular necks and to better simulate the in vivo loading/resting periods of the implant.…”
Section: Mechanical Tests Protocolmentioning
confidence: 99%
“…In literature, there are several experimental and numerical studies focusing on the fatigue analysis of hip implants (Baleani et al, 1999;Hedia et al, 1996;Kayabasi and Ekici, 2007;Li et al, 2002;Nganbe et al, 2011;Ploeg et al, 2009;Raimondi and Pietrabissa, 1999;Senalp et al, 2007). For 3 example, fatigue loading conditions, ISO 7206/3, have been applied to a hip stem to predict its elastic stress via large deflection finite element analysis (Ploeg et al, 2009).…”
Section: Introductionmentioning
confidence: 99%